2018
DOI: 10.3899/jrheum.180393
|View full text |Cite
|
Sign up to set email alerts
|

Utility of Anakinra in Acute Crystalline Diseases: A Retrospective Study Comparing a University Hospital with a Veterans Affairs Medical Center

Abstract: Objective.To evaluate the efficacy and safety of anakinra in inpatient management of acute gout and pseudogout.Methods.Hospitalized patients with acute gout (n = 77) or pseudogout (n = 11) or both (n = 3) were analyzed for response to anakinra and adverse effects.Results.Half of all patients had comorbidities limiting the treatment choice. Anakinra was well tolerated, and 92% of gout flares and 79% of pseudogout flares responded to treatment.Conclusion.Anakinra is an effective and safe treatment for acute gout… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 10 publications
0
14
0
Order By: Relevance
“…The standard anakinra dosing is derived from the pilot study by So, et al, in which individuals with acute gouty arthritis were given anakinra 100 mg subcutaneously daily for 3 doses 8 . Several observational studies, including one from our center, have demonstrated the rapid efficacy of anakinra on pain and swelling in acute gout attacks [9][10][11][12][13][14][15][16][17][18] . The observational data for CPP crystal arthritis have been more limited, but anakinra has also been shown to be effective for acute episodes as well as maintenance therapy 14,19,20,21,22,23,24 .…”
mentioning
confidence: 99%
“…The standard anakinra dosing is derived from the pilot study by So, et al, in which individuals with acute gouty arthritis were given anakinra 100 mg subcutaneously daily for 3 doses 8 . Several observational studies, including one from our center, have demonstrated the rapid efficacy of anakinra on pain and swelling in acute gout attacks [9][10][11][12][13][14][15][16][17][18] . The observational data for CPP crystal arthritis have been more limited, but anakinra has also been shown to be effective for acute episodes as well as maintenance therapy 14,19,20,21,22,23,24 .…”
mentioning
confidence: 99%
“…Seven of the ten relevant articles found in the search were retrospective studies and were discounted because of possibility of researcher bias due to the methodology of chart review and lack of control groups. [2][3][4][5][6][7][8] One article, Balasubramaniam et al, was a protocol study for a potential randomized controlled trial with no results published at this time. 9 The remaining two articles were clinical trials.…”
Section: Related Literaturementioning
confidence: 99%
“…4 Interleukin-1 (IL-1) antagonism, using the IL-1β-specific antibody canakinumab, is approved in Europe for gout flare. Off-label prescription of the soluble IL-1 receptor antagonist anakinra has been reported effective in case series, [5][6][7][8][9][10] including in hospitalized inpatients. [11][12][13][14] Anakinra was noninferior to conventional approved therapies for acute gouty arthritis in a recent controlled trial.…”
Section: Introductionmentioning
confidence: 99%